Expansion of the Benefits Package : The Experience of Armenia - Lavado, Rouselle F. (World Bank, Washington, DC, 2018)
The legacy of the Semashko system left Armenia with an oversized and overstaffed health system. Beginning in the 1990s the country focused on re-designing its health system in an attempt to rationalize resources. In order to improve the efficiency, access and quality of health care service provision, the Government undertook supply-side reforms. These reforms included: (a) strengthening Primary Health Care (PHC) provision; (b) downsizing excess hospital capacity; and, (c) changing provider payment mechanisms and introducing a purchaser-provider split.Armenia introduced the Basic Benefit Package (BBP) in 1999 for the socially vulnerable population to target the so-called socially important diseases. The package utilizes public resources to finance, through provider contracts, PHC and emergency services for all Armenian citizens, with co-payment exemptions for the poor and vulnerable. In addition, selected inpatient services are provided for free for the poor, vulnerable and other specific categories.Unfortunately, low public health spending levels and incomplete demand-side health financing reform have resulted in serious shortcomings in financial risk protection outcomes. Armenia’s public health financing is among the lowest in the region. High co-payments for BBP covered services, lack of in-patient care coverage for the non-vulnerable population and outpatient pharmaceuticals for all, have resulted in household out-of-pocket (OOP) spending being the predominant source of financing for health in the country. As Armenia is grappling with an aging society and a health care system struggling to adjust to morbidity and mortality epidemiological changes, its path to Universal Health Coverage (UHC) requires increased funding from prepaid pooled sources in order to sustain and make further progress on improving population health outcomes and financial risk protection.This paper examines the Armenian health system, with a focus on the BBP program. It takes stock of implemented reforms and analyzes the pending agenda. The paper is organized as follows. Section two provides a general overview of Armenia’s health system, focusing on financing and health service delivery. Section three describes the BBP program including its institutional architecture, beneficiary targeting, BBP services and fund management, and related information dissemination. Section four discusses the sustainability of the BBP program amidst economic, epidemiologic, and demographic challenges. The last section focuses on the pending agenda related to targeting, integrated care, and coverage of the non-vulnerable population.